Management Policy and Implementation in Improving The Quality of Higher Education in Indonesia - Nasution, Putra Mahendra Gunawan; Mesiono, Mesiono (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This study aims to determine the policy and implementation of management in improving the quality of education in Indonesian universities. This research uses a literature research method with a qualitative descriptive approach. Literature, scientific journals are needed to study and search for data sources. The results of this study explain the quality assurance approach directing higher education institutions to learn and implement Total Quality Management (TQM). There have been four successes within the scope of college management, among others: (1) Students are satisfied with the services provided by the College; (2) Education customers are satisfied with the services provided to their students; (3) stakeholders are satisfied to have qualified graduates and according to expectations; (4) Lecturers and education staff are satisfied with the services of universities in several fields: division of labor, relationships and communication between lecturers/leaders.